Pelatihan Mindset Sociopreneur dan Aqad Syari’ah Bagi Tenant Fakultas Teknologi Industri Universitas Ahmad Dahlan - Farid Ma'ruf Farid Ma'ruf; Jefree Fahana; Syifa Fitriani; Amalya Nurul Khairi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
PPK FTI activities is a manifestation of the application of one of the faculty visions, namely entrepreneurship, which is then also supported by ristekbrin through a community service funding scheme. One of the outputs of this activity was to produce 6 viable tenants and became the essential thing in this PPK FTI activity. Several stages were passed, starting from administrative selection until 20 tenants were obtained to participate in the training which would later be selected again into 6 tenants. Sociopreneur mindset training is important in this KDP activity because, in addition to the spirit of empowerment, doing business must also provide benefits to others. In addition, sharia aqad is also a training material because buying and selling aqad is the key to the start of the business process where to be taken. In essence, doing business is about the benefits of the world and savings in the afterlife. Some obstacles were experienced during online training, such as signals and voices, but these did not dampen the tenant's enthusiasm for participating in the training. Most of the tenants were able to receive well and were satisfied with the training material so that it could be practiced in their entrepreneurial activities.